Pemberdayaan Keluarga Sebagai PMO (Pengawas Minum Obat) Bagi Penderita TB di Wilayah Kecamatan Medan Sunggal - Indrawati; Elfira, Eqlima; Harahap, Sholihuddin (Jurnal Pengabdian kepada Masyarakat Radisi, 2024)
TB control efforts are carried out by implementing the DOTS (Directly Observed Treatment Short-course) strategy which is a short-term treatment with direct supervision. To ensure regularity of treatment, a supervisor of taking medicine (PMO) is needed, namely the family. The team conducted health education activities for 30 families who have TB patients at home in Medan Sunggal District. The method used was direct counselling accompanied by questions and answers with the family. Activities were carried out that aimed to provide directed education to families who have TB patients at home to remember to always take medicine. Feedback from this activity is that families understand and recognize the signs and symptoms of TB due to forgetting to take medicine and the role of supervision in taking medicine is very important in supporting their recovery.